Green Marketing Mix Drives Customer Loyalty Amid Low Environmental Awareness: Campuran Pemasaran Hijau Meningkatkan Loyalitas Pelanggan di Tengah Rendahnya Kesadaran Lingkungan - Intan Dwi Isma Saputri; Sonja Andarini (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Environmental degradation from plastic waste has intensified global attention on sustainability, prompting companies to adopt eco-conscious business practices. Specific Background: In Indonesia, urban coffee shop industries increasingly integrate green strategies to attract environmentally aware consumers. However, the direct influence of environmental awareness and the green marketing mix on customer loyalty remains underexplored, particularly among local coffee brands. Knowledge Gap: Prior research focused primarily on retail and fast-food sectors, leaving a gap in understanding how sustainability-driven marketing impacts loyalty in local coffee businesses. Aims: This study investigates the effect of environmental awareness and the green marketing mix on customer loyalty at Fore Coffee MERR Surabaya. Results: Using a quantitative approach with 100 respondents and multiple linear regression analysis, findings reveal that both variables jointly have a positive and significant effect on customer loyalty (R² = 0.483), though only the green marketing mix shows a significant partial effect (β = 0.764, p < 0.001). Novelty: This study extends green marketing literature by evidencing its role as a primary driver of loyalty in sustainable coffee businesses, despite limited environmental awareness influence. Implications: The results highlight the importance of consistent green marketing strategies and sustainability communication to strengthen long-term customer engagement and loyalty. Highlights: Green marketing significantly strengthens customer loyalty. Environmental awareness alone shows limited influence. Consistent sustainability communication enhances brand trust. Keywords: Environmental Awareness, Green Marketing Mix, Customer Loyalty, Sustainable Business, Fore Coffee